ZOOXANTHELLAE DENSITY IN DIFFERENT ZONE AND LIFE FORM IN INNER AND OUTER ZONE OF SPERMONDE ISLANDS - Tombi Bara'langi', Lorenzo Noris; Tuwo, Ambo; Yusuf, Syafyudin; Rani, Chair; A. Ala Husain, Aidah; Tresnati, Joeharnani (Jurnal Ilmu Kelautan SPERMONDE, 2021)
The Spermonde Islands are part of the mega diversity area in the world's coral triangle area, crossed by the Wallace line. The Spermonde Archipelago consists of 120 islands spread over four zones: the inner zone, middle inner zone, middle outer zone, and outer zone. Samalona Island is located in an inner zone with a high level of eutrophication, and Langkai Island is located in an outer zone with a high brightness level. This study aims to determine whether there are differences in zooxanthellae density in various life forms and coral reef zones in the inner and outer zones of the Spermonde Islands. Coral sampling was done at coral reef ecosystems on Samalona Island and Langkai Island using SCUBA tools, cutting tools, and plastic samples. The zooxanthellae were separated from their hosts using a modified airbrush sprayer with an air pressure of 3000 psi. The zooxanthellae density was calculated using the formula of Eaton et al. Water qualities were measured in-situ using the water quality checker. The data were analyzed using factorial analysis with two factors. This study indicates that the zooxanthellae density in the folios life form is higher than in the encrusting and branching life forms. This study indicates that: (1) the zooxanthellae density in the same life form is not significantly different between the inner zone and outer zone; (2) the comparison of the zooxanthellae density in the same coral reef zone was not significantly different between the inner and outer zones; (3) the comparison of zooxanthellae density in the same coral reef zone was significantly different between life forms in the inner zone (Samalona Island); (4) the comparison of the zooxanthellae density in the same coral reef zone was significantly different between the life forms in the outer zone (Langkai Island).